KOMBINASI UV SOLAR DRYER DAN SOLAR AIR HEATER UNTUK PENGERINGAN IKAN - Gusnawati Gusnawati; Verdy A. Koehuan; Laurensius Longo Sogen (Universitas Nusa Cendana, 2023)
Fish as a source of animal protein is a fishery commodity that is prone to quality deterioration and spoilage after the fish is caught, so it needs fast, precise and correct handling to keep its quality in the hands of consumers. There for it is necessary to have a process that extends the durability through drying. One drying alternative is to use a Solar Air Heater with an Ultra Violet (UV) Solar Dryer drying house by making a building made of transparent material that functions as an insulator so that the solar irradiation trapped in the building will increase its temperature. The accumulated heat is used to dry the fish. Sardines that have just been displayed are put into the drying chamber with various loads of 22.23 kg, 14.82 kg and 7.41 kg. The energy source for drying is from sunlight with the Solar Air Heater system. The results show that drying efficiency and thermal efficiency increase with the addition of drying load. The highest values ​​of drying efficiency and drying house efficiency occurred at the mass load of 22.23 kg of fish at 13.17% and 50.57% with the lowest specific energy consumption (KES) of 18947.421 kJ/kg. The average temperature and temperature difference both in the solar air heater and in the drying chamber increase with the addition of the drying load. This temperature increase increases the drying rate which can reduce the drying time.